Effectiveness of the Talaqqi Method in Memorizing the Quran - Dinda Amartia Sari; Dasrizal Dasrizal; Fauza Masyhudi; Darwati Darwati; Isnadul Hamdi; Lusiana Desvia (Journal of Theory and Research Memorization Quran, 2025)
This study aims to evaluate the effectiveness of the talaqqi method in improving students' ability to memorize the Quran. The talaqqi method which is one of the traditional methods in memorizing the Quran involves direct interaction between the teacher (murshid) and the student in the process of repeating and correcting the reading. This case study was conducted at one of the Islamic educational institutions that focus on teaching Alquran memorization in Indonesia. This research uses qualitative methods with data sources taken through field observations, interviews with students and teachers, and analysis of student memorization achievements. The results showed that the talaqqi method effectively strengthens students' memorization and improves tajweed and makhrarijul huruf. It also improves learning discipline and emotional engagement between teachers and students, which has a positive impact on the memorization process. Although this method requires high time intensity and close supervision, the long-term benefits in forming strong and consistent memorization are felt by students. This study concludes that the talaqqi method can be an effective approach in learning to memorize the Quran provided there are competent teachers and a conducive learning environment.